Wine stress vs. Technostress: Communities and wine appreciation digital platforms - Biot-Paquerot, Guillaume; Dubois, Magalie (BIO web of conferences, 2023)
In this conceptual article, we propose to investigate the intrinsic motivations of wine appreciation platform user communities, such as Vivino. By helping to reduce the stress linked to the complexity of the purchasing and tasting experience, which we call wine stress, these technologies increase the pleasure of participating in the community and gamify the sharing of knowledge via the platform. At the same time, exposing the user both to social exposure within the community of wine enthusiasts, and thus to peer judgment, but also to cognitive dissonance in the tasting experience.